The Impact of Section 12J Venture Capital Companies' Regime on Small and Medium Enterprises in South Africa - Makhalemele, Moeketsi (Graduate School of Business (GSB), 2021)
This study sought to examine whether the use of tax incentives to boost investment into the SME sector is an effective policy for economic development. More specifically, the study focused on the Section 12J tax incentive of the Income Tax Act of South Africa, which underpins the current venture capital companies' (VCC) regime for this country. This VCC regime is aimed at addressing the challenge of lack of access to finance by SMEs, and it does so by incentivising venture capital investors to provide equity capital to qualifying SMEs. These SMEs are, in turn, expected to grow and help reduce the economic challenges of poverty and unemployment in South Africa. A mixed methods research approach was adopted for this study. It was also inductive in nature, based on primary data collected from a survey of various stakeholders of the VCC regime using a convenience sampling method. The data variables of the study were based on factors relating to the impact that the VCC regime has had on SMEs in terms of financial performance and creation of decent employment. The study concludes that the VCC regime has had a positive impact on the South African SME sector in terms of financial performance and creation of decent employment. As a result, the VCC regime has shown to be an effective tool for addressing various economic challenges, such as: lack of access to finance faced by SMEs, high failure rate of SME businesses, and poverty alleviation through provision of decent employment by SMEs. Thus, the resultant recommendation submitted in the study is that the VCC regime should as such be extended beyond its current sunset date in order to ensure the South African economy continues to enjoy the benefits that the regime has to offer.